Adherence to doxycycline for uncomplicated genitourinary chlamydia: A prospective observational study - Daniel Ridelman; Shira Heisler; Angela Groves (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Since 2020, the Center for Disease Control and Prevention (CDC) no longer recommends single‐dose azithromycin as first‐line therapy for uncomplicated genitourinary chlamydia, advising instead a 7‐day course of doxycycline. Our study investigates self‐reported adherence to the new regimen, reasons for nonadherence, and the impact of dispensing the regimen on‐site compared to prescribing it. Methods We performed a prospective observational study of adult patients treated for suspected or laboratory‐confirmed uncomplicated genitourinary chlamydia at three urban emergency departments (EDs), where patients receive a prescription for doxycycline, and in a sexually transmitted infection (STI) clinic, where the 14 doxycycline pills are dispensed on‐site. Clinical data were extracted from electronic medical records and patients were interviewed regarding adherence via telephone 2–4 weeks after their index visit. Results We enrolled 127 STI clinics and 201 ED patients. Therapeutic adherence was reported by 85% of STI clinic patients and 77% of ED patients. In the ED setting, younger age and female sex were associated with nonadherence, with only 67% of female patients reporting adherence. Reported reasons for nonadherence included medication adverse effects, financial and transportation barriers, skepticism of the need for therapy, and misunderstanding of discharge instructions, among others. Conclusion A considerable portion of patients treated for uncomplicated genitourinary chlamydia in urban EDs and STI Clinics report nonadherence to the 7‐day doxycycline regimen. The CDC recommendation to consider azithromycin when nonadherence is a “substantial concern” should be applied broadly in these settings by routinely discussing barriers to adherence when selecting the optimal antimicrobial regimen. The benefit of dispensing the doxycycline regimen on‐site compared to prescribing it could not be determined given differences in baseline characteristics between the two groups.